IgG AND CD4+ Responses Post Immunization With Cidr1α-Pfemp1 Recombinant Protein - Nurul Istinaroh; Erma Sulistyaningsih; I Dewa Ayu Ratna Dewanti (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2024)
Malaria vaccine is urgently needed to eradicate malaria. The complexity of Plasmodium sp life cycle and host immunity to malaria have become the forces for developing peptide-based malaria vaccines using recombinant technology. The CIDR1α-PfEMP1 (cysteine-rich interdomain region 1α of Plasmodium falciparum erythrocyte membrane protein 1) is vital in malaria pathogenicity, making it a malaria vaccine candidate. This study investigated the IgG and CD4+ responses generated after the CIDR1α-PfEMP1 recombinant protein immunization in Wistar rats. The rats were divided into a control group, injected with 0.9% NaCl, and a treatment group, subcutaneously injected with 150 µg of purified CIDR1α-PfEMP1 recombinant protein. Injection was conducted thrice with a three-week interval. Blood samples were extracted every two weeks after immunization. IgG and CD4+ concentrations were measured using ELISA. Data were analyzed using the independent T-test and Mann-Whitney test based on the data distribution. IgG and CD4+ concentrations increased along with the injection frequency. Significant differences between the control and treatment groups were observed in IgG concentrations after all injections and CD4+ level only after secondary II immunization (p<0.05). In conclusion, the CIDR1α-PfEMP1 recombinant protein induces humoral and cellular immune responses through increased IgG and CD4+ concentrations, making it a potential malaria vaccine candidate.